High-dose chemotherapy with autologous peripheral blood stem cell transplantation for bone and soft-tissue sarcomas - Kasper, Bernd; Lehnert, T.; Bernd, Ludger; Mechtersheimer, Gunhild; Goldschmidt, Hartmut; Ho, Anthony Dick; Egerer, Gerlinde (Bone marrow transplantation, 2004)
The role of high-dose chemotherapy (HDCT) with PBSCT in the treatment of bone and soft-tissue sarcomas is not established. In total, 27 patients (15 female, median age at TPL 30.6 years (range: 13-59)) were analyzed (Ewing sarcoma family n=8, osteosarcoma n=6, MPNST (malignant peripheral nerve sheath tumor) n=4, synovial sarcoma n=3, liposarcoma n=2, leiomyosarcoma n=2, rhabdomyosarcoma n=1, meningosarcoma n=1). Following chemotherapy and surgery complete remission (CR) (n=9), partial remission (PR) (n=10), stable disease (SD) (n=2) and progressive disease (PD) (n=6) were reached prior HDCT. Different HDCT conditioning regimens were used. One patient died due to cardiac arrest after HDCT. Except hematologic side effects, no WHO grade III-IV complications were observed. Four patients died within 6 months due to PD, disease recurred in another seven patients and led to death, 15 patients are alive with/without disease. The median progression-free survival (PFS) is 12.0 months (range: 0-58), in nine CR patients median PFS is 25.8 months (range: 3-58). Although the role of HDCT in the treatment of sarcomas is not defined, a subgroup of patients who achieved CR before HDCT could benefit from this therapy.